Rapid evolution from "normal" left ventricular outflow tract to fatal subaortic stenosis in infancy. Issue 5 (May 1981) - Freedom, R M; Fowler, R S; Duncan, W J
Abstract : Serial clinical, echocardiographic, haemodynamic, and angiocardiographic data support the conclusion that over four months severe discrete subaortic stenosis evolved from a previously angiocardiographically normal left ventricular outflow tract in an infant who had a successful repair of thoracic aortic coarctation. This case supports those who suggest that a myocardial factor may play an important role in the change in form and function of some congenitally malformed hearts.